Consolidation, Construction and Fashioning of a « Self », or the Way in which Language Models a given Reality. (The Case of the Letters of Relation of Hernán Cortés) - Espitia Ortiz, David Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The present study uses concrete examples to give a detailed analysis of the way in which conquistadores and cronistas [chroniclers] fashioned their “self”, with the objective of convincing a real and virtual receptor that their behaviors regarding the events were justified. For this, each author makes adecuate use of an expressive form –within a concrete genre system- that corresponds both to his own interests and to those of the receptor. It is clear that in the generic system of the XVI centruy, two forms allowed the presence of the «self» without loss of decorum: the letter of relation, and the relación de sucesos[report of events].